Agent of change: print culture studies after Elizabeth L. Eisenstein - Baron, Sabrina A. (Studies in print culture and the history of the book, 2007)
Errata lists and the reader as corrector / Ann Blair -- Counterfeit printing as an agent of diffusion and change : the French book-privilege system and its contradictions (1498-1790) / Jean-Dominique Mellot -- On the threshold : architecture, paratext, and early print culture / William H. Sherman -- Moving pictures : Foxe's Martyrs and Little Gidding / Margaret Aston -- Humphrey Moseley and the invention of English literature / David Scott Kastan -- "On the behalf of the printers" : a late Stuart printer-author and her causes / Paula McDowell -- Fixity versus flexibility in "A song on Tom of Danby" and Dryden's Absalom and Achitophel / Harold Love -- Reinventing Gutenberg : woodblock and movable-type printing in Europe and China / Kai-wing Chow -- Scotland : international politics, international press / Arthur Williamson -- Change and the printing press in sixteenth-century Spanish America / Antonio Rodríguez-Buckingham -- The southern printer as agent of change in the American revolution / Calhoun Winton -- The printing press and change in the Arab world / Geoffrey Roper -- Print and the emergence of multiple publics in nineteenth-century Punjab / Vivek Bhandari -- "Ki ngā pito e whā o te ao nei" (to the four corners of this world) : Maori publishing and writing for nineteenth-century Maori-language newspapers / Jane McRae -- "Little jobs" : broadsides and the printing revolution / Peter Stallybrass -- What difference does colonialism make? : reassessing print and social change in an age of global imperialism / Tony Ballantyne -- The laser printer as an agent of change : fixity and fluxion in the digital age / Barbara A. Brannon -- The cultural consequences of printing and the Internet / James A. Dewar and Peng Hwa Ang -- Seeing the world in print / Robert A. Gross -- The printing revolution : a reappraisal / Roger Chartier